Ultrasound Assisted Endoscopic Gastric Bypass (USA-EGB): a potential endoscopic alternative to surgical bypass, a pre-clinical proof of concept study - Kadkhodayan, Kambiz; Viana, Artur; Singh, Sanmeet; Cosgrove, Natalie; Jain, Deepanshu; Yang, Dennis; Arain, Mustafa A; Irani, Shayan; Hasan, Muhammad Khalid (Endoscopy International Open, 2023)
Background and study aims Endoscopic weight loss procedures have gained traction as minimally invasive options for the primary treatment of obesity. Thus far, we have developed endoscopic procedures that reliably address gastric restriction but result in significantly less weight loss than surgical gastrointestinal bypass. The goal of this nonsurvival study was to assess the technical feasibility of an endoscopic procedure, that incorporates both gastric restriction and potentially reversible gastrointestinal bypass.Methods Ultrasound-assisted endoscopic gastric bypass (USA-EGB) was performed in three consecutive live swine, followed by euthanasia and necropsy. Procedure steps were: 1) balloon-assisted enteroscopy that determines the length of the bypassed limb; 2) endoscopic ultrasound-guided gastroenterostomy that creates a gastrointestinal anastomosis using a lumen apposing metal stent; 3) endoscopic pyloric exclusion that disrupts transpyloric continuity resulting in complete gastrointestinal bypass; and 4) gastric restriction that reduces gastric volume.Results Complete gastrointestinal bypass and gastric restriction was achieved in all three swine. The mean total procedure time was 131 minutes (range 113–143), mean length of the bypassed limb was 92.5 cm and 180 cm, using short and long overtubes, respectively. There were no significant complications.Conclusions We successfully described USA-EGB in three consecutive live swine. Further studies are needed to access the procedures safety, efficacy, and clinical use.